The absorbing haloes of high-redshift radio galaxies and Ly alpha blobs - Wilman, R (2006)
Results are summarized from a program of VLT-UVES echelle spectroscopy on the HI Ly alpha absorption in z > 2 radio galaxies. The nature and incidence of this absorption are reviewed, along with scenarios for its origin. Comparison is made with integral field spectroscopy of the two radio-quiet 100 kpc-scale Ly alpha haloes in the z = 3.09 SSA22 protocluster-the Steidel Lya alpha blobs. The emphasis is on using such absorption to study the injection of energy and metals from radio jets and starburst superwinds, processes considered vital to the formation of the most massive galaxies.